Inclusion of students with disabilities in schools of application: perspective of its directors - Régis Henrique dos Reis Silva; Thiago Vaz Santiago (Universidade Federal de Santa Maria (UFSM), 2010)
This study has as its central theme the enrollment of students with disabilities in Colleges Application of Federal Institutions of Higher Education (CAP/IFES). Its general purpose is to analyze the situation experienced by students with disabilities in the CAP/IFES in view of its directors on national policies for Special Education. This research is characterized as a field study of analytical-critical and is bounded to fifteen CAP/IFES. The study population was composed of directors of CAP/IFES, who performed this function in the first half of 2008. We sent questionnaires (semistructured) for all principals of the schools mentioned above, of which ten (66.7%) were actually answered. For analysis of the questionnaires it was found and the percentage content of the replies submitted by the directors. The data indicate the precise number of disabled students enrolled in the CAP/IFES and the situational reality of these students, according to the vision of the directors of these institutions. The directors also reported their conceptions of school enrollment and the main difficulties experienced by institutions that drive before the challenge presented by national policies of Special Education. Among these difficulties we highlight the lack of training for educators, which hinders the understanding and critical analysis of ideas inclusivist, making it difficult to overcome retrograde practices (explicit or implicit) that increase the educational and social exclusion of disabled students and new generations.